Calcific myonecrosis - J.L.E Tai; W T van de Kreeke; H.K.M de Greve (Journal of the Belgian Society of Radiology, 2011)
Background: A 71-year-old man presented with a slow-growing mass for the past 6 years in the right lower leg. He had a history of a motor vehicle accident as a 12-year-old boy, when a truck ran over his legs. He had already undergone a trans-tibial amputation of the left leg 24 years earlier.